The Whole Child: Restoring Wonder to the Art of Parenting - Carey, Seamus (Rowman & Littlefield Publishers, 2003)
The Whole Child is a beautifully written book combining classic philosophical themes like wonder and happiness with modern parenting virtues like courage, compassion, integrity, and discipline. Seamus Carey uses anecdotes from his own experience as a parent, some amusing and some poignant, to illustrate philosophical concepts. The result is a rare work, as valuable to the serious student of philosophy as it is to Carey's fellow parents. Carey argues that parents need to rediscover the sense of wonder—the ontological depth—with which children experience life, and offers suggestions for how this recovery might take place. In so doing, Carey uncovers standards and ideas for raising children that reach beyond those typically considered by the modern family.